Health‐related quality of life in cutaneous T‐cell lymphoma: A cross‐sectional survey study - M.M. Shinohara; H.M. Mahurin; E. Tarabadkar; D.S. Hippe; K. Lachance; E.J. Kim; E.T. Loggers (Wiley, 2021)
Summary Background Patients with cutaneous T‐cell lymphoma (CTCL) often have indolent but symptomatic disease. Objective Assessment of the health‐related quality of life (HRQoL) of patients with CTCL. Methods Cross‐sectional survey study. HRQoL was measured by Skindex‐16 and FACT‐G. Results A total of 372 responses were received; 80 incomplete/ineligible responses were excluded. A majority of respondents identified as white (87%; 250/288) and female (67%; 193/286) with a mean age of 57 ± 14 years. Most patients had early‐stage (IA-IIA) (74%; 162/203) mycosis fungoides (87%; 241/279). There were 33 (12%; 33/279) patients with Sézary syndrome. Mean itch score (visual analogue scale; VAS) was 3.2 ± 2.8, overall; 2.7 ± 2.6 for early, and 4.2 ± 2.9 for advanced disease (p = 0.008). Thirty‐eight percent (108/284) and 24% (69/284) reported head/neck and groin/genital involvement, respectively. Overall HRQoL was 46 ± 27 (Skindex‐16) and 71 ± 19 (FACT‐G), with worse HRQoL for patients with advanced versus early disease (Skindex‐16: 67 vs. 40; p=<0.001, FACT‐G: 62 vs. 76; p = 0.001). Predictors of worse HRQoL included head/neck, hand/foot or groin/genital involvement, younger age and spending >15 min daily treating CTCL. Limitations Include anonymous survey methodology, underrepresentation of certain CTCL subtypes and non‐white respondents. Conclusions Patients with CTCL, particularly those with advanced disease or involvement of the head/neck, acral or groin/genital sites, experience significant impact on HRQoL.